A shading effects framework for comics - Hsiao, Yu (2014)
Shading is a process in which shades of objects are drawn with different levels of darkness to create lifelike drawings. As technology advances, comic drawing is created gradually on the internet platform. Therefore, a need for creating quality shading effect for computer artworks was identified for this project.